Medial frontal gyrus alterations in schizophrenia: Relationship with duration of illness and executive dysfunction. Issue 2 (28th February 2015) - Frascarelli, Marianna; Tognin, Stefania; Mirigliani, Alessia; Parente, Fabrizio; Buzzanca, Antonino; Torti, Maria Chiara; Tinelli, Emanuele; Caramia, Francesca; Di Fabio, Fabio; Biondi, Massimo; Fusar-Poli, Paolo
Abstract: Executive functioning is consistently impaired in schizophrenia, and it has been associated with reduced gray matter volume in prefrontal areas. Abnormalities in prefrontal brain regions have also been related to the illness duration. The aim of the study was to investigate the effect of executive functioning decline and chronicity in prefrontal regions of patients with schizophrenia. Participants comprised 33 schizophrenic patients, 18 with duration of illness (DoI) shorter than 10 years and 15 with duration of illness longer than 10 years. In addition, 24 healthy controls served as a comparison group. Participants performed the Wisconsin Card Sorting Test (WCST) and underwent structural magnetic resonance imaging. Patients with longer DoI showed significant reduction of gray matter volume in the left medial frontal gyrus compared with healthy controls. Moreover, there was a trend for greater gray matter volume decrease in patients with a longer illness duration compared with patients with shorter illness duration. There was no interaction between the volume of the left medial frontal gyrus performance on the WCST. The present study supports the hypothesis that medial frontal gyrus alterations in schizophrenia are sensitive to duration of illness. These alterations were not associated with executive functioning. Highlights: Left medial frontal gyrus significantly reduced in patients with longer duration of illness compared to healthy controls. Patients with longer duration of illness had intermediate left medial frontal gyrus volume compared to healthy controls and patients with longer duration of illness. Lack of interaction between the volume of the left medial frontal gyrus and the WCST performance.